2012
DOI: 10.3747/co.19.1068
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Choice of Maintenance Therapies in Non-Small-Cell Lung Cancer

Abstract: Platinum-based combinations currently remain the preferred approach in the first-line setting 5,6 . Further studies have also established a role for second-line and, in some instances, third-line therapy with agents such as docetaxel, pemetrexed, and erlotinib. These advances have resulted in median survivals of 10-12 months in contemporary studies.Although second-line therapies have improved overall survival, up to 50% of patients completing first-line treatment become ineligible for further treatment, mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Previous studies have identified response to first-line therapy, histology, physical functioning, and the presence of biomarkers as being influential to physicians’ MT recommendations [ 12 18 ]. Our study also identified response to first-line treatment as a key factor for physicians; however, surprisingly and contrary to NCCN guidelines, disease progression was not always a deterrent to a MT recommendation, based on the hypothetical profiles presented to physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified response to first-line therapy, histology, physical functioning, and the presence of biomarkers as being influential to physicians’ MT recommendations [ 12 18 ]. Our study also identified response to first-line treatment as a key factor for physicians; however, surprisingly and contrary to NCCN guidelines, disease progression was not always a deterrent to a MT recommendation, based on the hypothetical profiles presented to physicians.…”
Section: Discussionmentioning
confidence: 99%
“…This may represent the future for other histological subtypes such as SCC. Therefore, in addition to clinical epidemiological data, future molecular epidemiological data on LC in Brazil will be required to improve the balance of costs and to meet oncological demands [7,12].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in histological patterns in smokers and males from predominantly SCC to predominantly ACA, were reported in several countries [5,6,8,[9][10][11]. The histological type plays a role in defining the appropriate type of systemic treatment that should be implemented with the largest therapeutic arsenal being available for ACA; mainly in terms of targeted chemotherapy [7].…”
Section: Introductionmentioning
confidence: 97%